2012
DOI: 10.1002/chem.201101605
|View full text |Cite
|
Sign up to set email alerts
|

Tri‐ and Pentacalix[4]pyrroles: Synthesis, Characterization and Their Use in the Extraction of Halide Salts

Abstract: Calixpyrrole-based oligomeric compounds were synthesized by "click chemistry" from the corresponding alkyne- and azide-functionalized calix[4]pyrroles. Calix[4]pyrrole 3, possessing an alkyne functional group, was prepared through a mixed condensation of pyrrole with acetone and but-3-ynyl 4-oxopentanoate. Another alkyne-group-containing calix[4]pyrrole 5 was obtained by treatment of 4'-hydroxyphenyl-functionalized calixpyrrole 4 with propargyl bromide. Tetrakis(azidopentyl)-functionalized calix[4]pyrrole 7 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…The preparation of the starting material 6 was carried out by coupling under basic conditions of a phenol substituted calixpyrrole 4 with 4-nitrophthalonitrile 5 13 . Calixpyrrole 4 having the hydroxyphenyl substituent was obtained by random cyclotetramerization of pyrrole (1), acetone (2) and 4-hydroxyacetophenone (3) in 4:3:1 molar ratio in methanol under acid catalysis 14 . Flash column chromatography with proper eluents was used in the purification of the compound 4 (see experimental section) and column chromatography was used for purification of compounds 7 and 8.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The preparation of the starting material 6 was carried out by coupling under basic conditions of a phenol substituted calixpyrrole 4 with 4-nitrophthalonitrile 5 13 . Calixpyrrole 4 having the hydroxyphenyl substituent was obtained by random cyclotetramerization of pyrrole (1), acetone (2) and 4-hydroxyacetophenone (3) in 4:3:1 molar ratio in methanol under acid catalysis 14 . Flash column chromatography with proper eluents was used in the purification of the compound 4 (see experimental section) and column chromatography was used for purification of compounds 7 and 8.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…5,[28][29][30] However, few examples of multi (more than two) calixpyrrole systems have been described to date, especially if we exclude examples in which calixpyrrole units were grafted onto either polymers or surfaces. Notable examples of multicalixpyrrole structures (three or more calix units) have been reported by Ballester 31 , Aoyan 32 and Kohnke. 33 As part of our work on the host-guest chemistry of bis-and tris-calix [4]pyrrole 27,33 receptors, we identified the anti-and syn-meso-1,3-(4-hydroxyphenyl)calix [4]pyrroles (anti-5 and syn-5 in Scheme 1) first reported by Lee 34 as useful precursors for the assembly of multi-component structures.…”
Section: Introductionmentioning
confidence: 96%
“…These valuable studies include expanded, 20 N-confused, 21,22 C-rim modified 23 chromophore and fluorophore modified, 24−27 functionalized nanoparticles, 28−30 and redox active calix [4]pyrrole derivatives. 31,32 In addition to proven ion-pair recognition ability, 18,33 well-defined oligomers 34 and polymers 35−38 of calix [4]pyrroles have also been reported and it was shown that these macrocyclic anion receptors can be used for the extraction of F − and Cl − anions, in the form of their tetrabutylammonium salts, from aqueous solutions. Moreover, enhanced extraction of KF and KCl from aqueous solutions has also been shown when the crown ether moieties were incorporated into the polymer matrix along with calix [4]pyrrole receptor sites.…”
Section: Introductionmentioning
confidence: 99%